Serviços e produtos informacionais: um estudo de caso no SISTEBIB/UFAM durante a pandemia da COVID-19. - Oliveira, Taiwany Rodrigues de (Brasil, 2021)
This study analyzed the offer of information services and products by the Library System of the Federal University of Amazonas (SISTEBIB/UFAM). It has a methodological characteristic as an exploratory and descriptive research, being divided into three stages: bibliographical survey in the literature in the area about information services and products; documentary analysis from the social media of the libraries that make up the SISTEBIB/UFAM and field research with the research subjects. The data collection carried out on the social media of the libraries took place with a time frame from March 2020 to October 2021 and the field research took place through an electronic questionnaire, sent by email, with open questions. The results revealed that social media were fundamental in the provision of information services and products during the COVID-19 pandemic, as they helped to publicize these services and products, in addition to maintaining a close relationship with library users. It is concluded that the offer of informational services and products were not affected in the COVID-19 pandemic and that SISTEBIB/UFAM managed to achieve its mission, even in the face of adversities caused by the pandemic.